A vinyl phenyl silicone resin, an injection moldable ceramic organic silicon fireproof material
The silicone framework is constructed by cross-linking of vinyl linear/branched phenyl silicone resin, and combined with inorganic materials to form an "embedded" anchor bolt, which solves the problem of insufficient temperature resistance of the existing copper strip insulating layer, and realizes ceramicized silicone fireproof materials with high heat insulation, high heat resistance and high physical strength, suitable for the protection of soft copper strips.
Patent Information
- Application Number
- CN202310239109.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The existing copper insulation layer has limited temperature resistance, is easy to decompose in high temperatures or flames, loses its insulation and fire resistance, and cannot meet the fire protection needs of the OEM.
A vinyl linear/branched phenyl silicone resin was developed to construct an organic silicone skeleton by crosslinking, and a "embedded" anchor bolt was formed by combining inorganic materials to improve the insulation, heat resistance and physical strength of the material, and reduce viscosity through injection molding process, which is suitable for the protection of soft copper rows.
It realizes high heat insulation, high heat resistance and high physical strength of the material, is suitable for the protection of soft copper strips, meets the fire protection needs of the OEM factory, and improves production efficiency.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, in particular to a vinyl phenyl silicone resin and an injection moldable ceramic organic silicon fireproof material. Background Art
[0002] With the rapid development of new energy vehicles, battery overheating has become one of the important problems that often occur in automobile after-sales. Overheating may cause the insulation layer on the surface of the copper busbar that connects the battery cells to age and fail, resulting in an arcing effect, causing a chain reaction of battery cells out of control, and then causing a fire. According to statistics, there have been 3,000 electric vehicle fire accidents in China in 2021, and the probability of fire has reached nearly 4%, which is several times that of fuel vehicles.
[0003] At present, heat insulation treatment of copper busbars is one of the effective methods to alleviate electric vehicle fires. The existing copper busbar insulation layer is mainly made of heat shrink tubing or insulating resin spraying. However, the heat shrink tubing and insulating resin have limited temperature resistance. When the battery is exposed to high temperature or flame during thermal runaway, it is easy to decompose and form ash, thereby losing its insulation and fireproof ability, and cannot meet the fire protection needs of the OEM. The improvement plan is to tie a layer of high-temperature resistant fiberglass tape on the outside of the insulating resin or heat shrink tubing, but the adhesive layer of the fiberglass tape is also prone to degradation and failure at high temperatures, and the insulation is reduced. In addition, the fiberglass tape will become brittle at high temperatures and easily peel off under the impact of high-temperature flames, resulting in insulation failure.
[0004] Ceramic silicone rubber is inherently heat-resistant and insulating, and when burned, the Si-O structure will be transformed into a continuous, anti-oxidation, insulating network of silica ash covering the surface of the combustible, which can not only prevent further ablation, but also provide a material basis for the subsequent ceramicization of the material. The mechanism by which this material can be ceramicized is to use the silica ash generated after the combustion of silicone rubber, and through the bonding and sintering effect of the glass flow at high temperature, a eutectic reaction occurs between the silica ash and the refractory filler in the material, generating a dense and high-temperature resistant ceramic layer with a certain strength, thereby achieving the purpose of flame retardancy, fire resistance and insulation. Therefore, ceramic silicone rubber is one of the more ideal high-temperature resistant insulating materials at present.
[0005] At present, the most common molding process for ceramic silicone rubber is compression molding. This process involves coating the copper busbar with uncured rubber, placing it in a hot mold, and then molding and curing it. However, the compression molding process is inefficient, and the overflow during the molding process causes a large amount of rubber loss. The product needs to be deburred after demolding, which makes it difficult to meet the production capacity requirements of the OEM. In addition, the compression molding process is not suitable for soft copper busbars. After compression molding, the product will undergo significant deformation, which is not conducive to the installation and use of the soft copper busbar.
[0006] In summary, it is of positive significance to develop a ceramic silicone fireproof material that has excellent thermal insulation, heat resistance and can be applied to soft copper busbars. Summary of the invention
[0007] In order to solve the above technical problems, firstly, the present invention provides a vinyl straight chain / branched phenyl silicone resin. By cross-linking the above two different types of vinyl phenyl silicone resins, a silicone skeleton with a unique embeddable cavity structure can be constructed, which can be used for "embedded" anchor bolts of inorganic materials, giving the material excellent thermal insulation, heat resistance and physical strength; at the same time, by controlling the molecular structure and molecular weight of the phenyl silicone resin, the viscosity can be reduced, making it suitable for injection molding processing, and the ceramic silicone fireproof material obtained can be used to provide protection for soft copper busbars. Secondly, the present invention provides an injection moldable ceramic silicone fireproof material, the raw materials of which contain modified hydrogen-containing silicone oil, vinyl straight chain / branched phenyl silicone resin, a variety of inorganic powders and a reaction rate regulator. After mixing, the system has low viscosity and good fluidity, and can be suitable for injection molding process. At the same time, the cured material has high thermal insulation, high heat resistance and high physical strength.
[0008] The specific technical scheme of the present invention is:
[0009] In a first aspect, the present invention provides an ethylene linear / branched phenyl silicone resin having the structural formula shown below:
[0010] Vinyl linear phenyl silicone resin A:
[0011]
[0012] Wherein, X=1-10, Y=3-10;
[0013] Vinyl linear phenyl silicone resin B:
[0014]
[0015] Among them, x=1-10, y=3-6.
[0016] Vinyl branched phenyl silicone resin C (alternating type):
[0017]
[0018] Among them, x=1-10, y=3-10, z=5-10, a=0-7 (more preferably 1-4).
[0019] Vinyl branched phenyl silicone resin D (block type):
[0020]
[0021] Among them, X=1-10, Y=3-10, Z=5-10, a=0-7 (more preferably 1-4).
[0022] The above-mentioned vinyl straight-chain phenyl silicone resin and vinyl branched-chain phenyl silicone resin of the present invention can be used as the raw material of injection-moldable ceramic organic silicon fireproof material after being combined, and its advantages are:
[0023] (1) The present invention utilizes two different types of raw materials, vinyl straight-chain phenyl silicone resin and vinyl branched phenyl silicone resin, and by controlling the degree of crosslinking and the size of crosslinking, can construct an organic silicon skeleton with a unique embeddable cavity structure, which can be used for "embedded" anchor bolts of inorganic materials, construct a ceramic system at the molecular design level, greatly improve the bonding force between the resin and the inorganic material, and improve the low-temperature ceramic-forming properties of the organic silicon resin and the inorganic material, thereby giving the material excellent thermal insulation, heat resistance and physical strength.
[0024] (2) The molecular weight of the vinyl linear / branched phenyl silicone resin of the present invention is appropriate, which can effectively reduce the viscosity of the system and is suitable for injection molding process. If the molecular chain of the vinyl linear / branched phenyl silicone resin is too long and the number of branches is too large, the molecular weight is too large, the intermolecular force is stronger, the flexibility of the molecular chain becomes worse, and the viscosity of the material becomes larger, which is not conducive to injection. If the density of the vinyl branches is too low, it cannot effectively form an embeddable cavity structure with the vinyl linear silicone resin, which affects the thermal insulation and physical strength of the material.
[0025] (3) The carbon chain length of the alkyl side groups in the vinyl branched phenyl silicone resin of the present invention is preferably 1-8, and more preferably 2-5. The reason is that we have found that when component A and component B are mixed and cured, alkyl side groups of appropriate lengths on different molecules can be entangled, thereby increasing the degree of cross-linking of the molecules, which is beneficial to improving the mechanical strength of the cured material. However, the length of the alkyl side groups needs to be appropriate. If the length is too short, the degree of entanglement is weak. If the length is too long, it is easy to cause the system viscosity to be too high, and injection molding cannot be performed.
[0026] Preferably, the preparation method of the vinyl linear phenyl silicone resin is as follows:
[0027] Vinyl straight-chain phenyl silicone resin A: Under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane and dimethyldiethoxysilane are mixed evenly, and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature to continue the reaction, and dimethylvinylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation. The temperature is raised to 140-160°C for structural reforming to obtain vinyl straight-chain phenyl silicone resin A.
[0028] Vinyl straight-chain phenyl silicone resin B: Under the protection of an inert gas with a water content of 0.05-0.1wt%, dimethyldichlorosilane and diphenyldiethoxysilane are uniformly mixed and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature to continue the reaction, and dimethylvinylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation. The temperature is raised to 140-160°C for structural reforming to obtain vinyl straight-chain phenyl silicone resin B.
[0029] In the above-mentioned preparation process of the present invention, chlorosilane is very active and decomposes when it encounters water vapor in the air to generate silanol and hydrogen chloride gas. Under acidic conditions, silanol will further undergo condensation reaction with alkoxysilane to produce small molecule organosilicon polymer and release ethanol. In order to control the hydrolysis rate of chlorosilane, the present invention chooses to be carried out under the protection of a water-containing inert gas (preferably nitrogen). It should be noted that the water content of the inert gas is crucial. An appropriate water content can allow chlorosilane to hydrolyze slowly. If the water content is too low, hydrolysis cannot occur smoothly; on the contrary, if the water content is too high, it is easy to cause the hydrolysis rate to be too fast, thereby causing the product to gel. At the same time, the inert gas continuously introduced can take out the generated hydrogen chloride gas, prompting the product to be generated continuously and steadily. After the end-capping agent is added dropwise, the inert gas protection needs to be withdrawn in time, otherwise it will affect the subsequent reaction.
[0030] The preparation method of the vinyl branched phenyl silicone resin is as follows:
[0031] Vinyl branched phenyl silicone resin C (alternating type): under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane, vinylalkyldichlorosilane with a side alkyl carbon number of 1-8, and dimethyldiethoxysilane are uniformly mixed, and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature, and trimethylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation. The temperature is raised to 140-160°C for structural reforming to obtain vinyl branched phenyl silicone resin C.
[0032] Vinyl branched phenyl silicone resin D (block type): under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane and vinylalkyldichlorosilane with a side alkyl carbon number of 1-8 are mixed uniformly, and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature and methylphenyldiethoxysilane is added, and the reaction is continued for a period of time, and trimethylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation, and the temperature is raised to 140-160°C for structural reforming to obtain vinyl branched phenyl silicone resin D.
[0033] The preparation process of the vinyl branched phenyl silicone resin of the present invention is the same as that of the vinyl straight-chain phenyl silicone resin.
[0034] In a third aspect, the present invention provides the use of the above-mentioned vinyl linear phenyl silicone resin and / or vinyl branched phenyl silicone resin in the preparation of injection moldable ceramic organic silicon fire retardant materials.
[0035] In a fourth aspect, the present invention provides an injection moldable ceramic organic silicon fireproof material, which is obtained by uniformly mixing components including component A and component B and then heating and curing; wherein:
[0036] The component A comprises the following raw materials: vinyl straight-chain phenyl silicone resin A and / or vinyl straight-chain phenyl silicone resin B, silicon powder, silazane-modified fumed silica, modified hydrogen-containing silicone oil 1, modified hydrogen-containing silicone oil 2, inorganic powder, and a reaction rate regulator.
[0037] The component B comprises the following raw materials: vinyl branched phenyl silicone resin C and / or vinyl branched phenyl silicone resin D, silicon powder, silazane-modified fumed silica, inorganic powder, adhesion promoter, and catalyst.
[0038] Preferably, the component A comprises the following raw materials in mass percentage: 15-30% of vinyl straight-chain phenyl silicone resin A and / or vinyl straight-chain phenyl silicone resin B, 0-2.5% of silicon micropowder, 0-2.5% of silazane-modified fumed silica, 0-5% of modified hydrogenated silicone oil 1, 0-5% of modified hydrogenated silicone oil 2, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of zinc borate, 5-15% of hollow glass microspheres, and 0-1% of a reaction rate regulator.
[0039] Preferably, the component B comprises the following raw materials in mass percentage: 10-35% of vinyl branched phenyl silicone resin C and / or vinyl branched phenyl silicone resin D, 0-2.5% of silicon micropowder, 0-2.5% of silazane-modified fumed silica, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of hollow glass microspheres, 0-5% of adhesion promoter, and 0.1-0.3% of catalyst.
[0040] The curing principle of the components A and B after mixing in the present invention is as follows (taking the vinyl straight-chain phenyl silicone resin A, the vinyl branched phenyl silicone resin C and the hydrogen-containing silicone oils H1 and H2 as examples):
[0041]
[0042] The advantages of the ceramic organic silicon fireproof material of the present invention are:
[0043] (1) The present invention utilizes two different types of raw materials, vinyl straight-chain phenyl silicone resin and vinyl branched phenyl silicone resin, to construct a unique embeddable cavity structure by controlling the degree of crosslinking and the size of the crosslinking. The inorganic powder can form an "embedded" anchor with the silicone resin, and a ceramic system can be constructed at the molecular design level, which greatly improves the bonding force between the resin and the inorganic powder, and improves the low-temperature ceramic-forming properties of the silicone resin and the inorganic powder.
[0044] (2) The present invention utilizes silazane to modify fumed silica, which can reduce the silanol content on the silica surface, reduce the molecular gap, reduce the oil absorption, and improve the tensile strength of the composite silicone resin; further utilize the surface interface, quantum size and other nano-characteristics of fumed silica to coat spherical alumina and other inorganic flame retardant powders to form a particle-type core-shell structure with alumina as the core and fumed silica as the shell (although alumina has hydroxyl groups on the surface, its dispersibility in the raw material system is not as good as silica, and it is easier to agglomerate and adsorb on the surface of silica, while silica is relatively easier to be evenly dispersed in the silicone oil-containing system of the present invention to form the above-mentioned core-shell structure, which can greatly improve the dispersibility of inorganic powders such as alumina in the silicone resin and avoid high viscosity of inorganic powders due to aggregation), reduce the interaction between different molecules in the system, and improve the fluidity of the raw materials, so that the raw materials are suitable for injection molding processing.
[0045] (3) In the hydrosilylation reaction of the curing stage, platinum catalysts such as Custer are very active, the reaction is violent, and the product is easy to gel. In order to control the reaction rate, it is usually necessary to add reagents that can slow down the reaction rate, but after these reagents are added, the rapid curing process requirements of injection molding cannot be met. Therefore, one of the key points of injection molding is to control the reaction rate and achieve rapid curing, that is, after reaching the reaction trigger temperature, the silicone resin is quickly molded to form a stable ceramic fireproof material. The solution provided by the present invention is: the concentration of 3,5-propyl-1-butyne-3-ol in the reaction system is controlled by reacting butyl succinic anhydride (phase transition temperature is 46°C) with temperature responsiveness and 3,5-propyl-1-butyne-3-ol which can slow down the reaction; when the temperature is higher than 50°C, butyl succinic anhydride changes from solid to liquid, thereby increasing the reaction rate with 3,5-propyl-1-butyne-3-ol and rapidly consuming 3,5-propyl-1-butyne-3-ol, thereby releasing the efficiency of the catalyst; and the target product organic acid generated by the reaction can further improve the efficiency of the catalyst, thereby realizing temperature responsiveness triggering catalytic rapid curing.
[0046] (4) The present invention utilizes the excellent heat insulation of hollow glass microspheres to reduce the heat conduction rate, prolong the high temperature contact time of the silicone material, reduce the carbonization rate of the silicone material, and improve the density of the ceramic layer. The ability of the hollow glass microspheres to not easily "gasify" is utilized to increase the overall residual amount of the silicone material after high temperature burning, and to increase the residue coverage rate of the coated metal surface; the melting ability of the hollow glass microspheres at high temperatures is utilized to improve the structural integrity of the ceramic layer.
[0047] Preferably, the mass ratio of component A to component B is 0.5-1.5:1.
[0048] Preferably, in the component A:
[0049] The molecular structural formula of the modified hydrogen-containing silicone oil is H1: Among them: M=1-5; N=2-10.
[0050] The molecular structural formula of the modified hydrogen-containing silicone oil II is H2: Among them: m=1-5; n=2-10.
[0051] The reason why the present invention controls the molecular structure and molecular weight of the modified hydrogenated silicone oil 1 / 2 within the above range is that phenyl has a shielding effect, and if the molecular weight is too low, the thermal insulation performance is poor. If the molecular chain is long and the molecular weight is high, the subsequent hydrosilylation reaction will be difficult or incomplete, affecting the cross-linking and curing effect of the resin. When the molecular weight is controlled within the above range, the viscosity of the system can be reduced as much as possible while maintaining the performance of the ceramic silicone material, which is conducive to injection molding.
[0052] Preferably, the reaction rate regulator is prepared by mixing butyl succinic anhydride and 3,5-propyl-1-butyn-3-ol with an excess of alcohol.
[0053] The reaction principle of the above reaction rate regulator is as follows:
[0054]
[0055] Preferably, in the component B: the adhesion promoter is obtained by uniformly mixing 0-30wt% of a titanate compound, 0-20wt% of KH151, 0-20wt% of KH560 and 20-50wt% of a vinyl linear phenyl silicone resin A and / or B, heating the mixture to 80-90°C, and distilling off low boiling points under reduced pressure after the reaction.
[0056] The function of each group in the adhesion promoter of the present invention is to utilize polar reaction groups such as epoxy and vinyl to enhance the molecular interaction force between the substrate (such as a metal substrate) and improve the adhesion ability.
[0057] Preferably, in the component B, the catalyst is a platinum catalyst.
[0058] In a fifth aspect, the present invention provides a method for preparing an injection moldable ceramic organic silicon fireproof material, comprising the following steps:
[0059] S1: Mix and stir the vinyl straight-chain phenyl silicone resin A and / or B, silicon powder, silazane-modified fumed silica, modified hydrogen-containing silicone oil 1, modified hydrogen-containing silicone oil 2, spherical alumina, mica powder, zinc borate, hollow glass microspheres, and a reaction rate regulator at a temperature below 40°C and a vacuum degree of -0.01 to -0.07 MPa to obtain component A.
[0060] S2: Preparation of component B: Mix and stir vinyl branched phenyl silicone resin C and / or D, silicon powder, silazane-modified fumed silica, spherical alumina, mica powder, hollow glass microspheres, adhesion promoter, and catalyst at a temperature below 40°C and a vacuum degree of -0.01 to -0.07 MPa to obtain component B.
[0061] S3: Mix component A and component B evenly, and heat to ≥50°C for curing.
[0062] Preferably, in S1 and S2, the average particle size of the spherical alumina is 80-120 microns, the average particle size of the mica powder is 10-20 microns, and the average particle size of the hollow glass microspheres is 50-80 microns.
[0063] Preferably, in S3, component A and component B are mixed evenly, heated to ≥50° C. for curing, and the curing is completed within 1 minute.
[0064] Compared with the prior art, the present invention has the following technical effects:
[0065] (1) The present invention utilizes two different types of raw materials, vinyl linear phenyl silicone resin and vinyl branched phenyl silicone resin, and can construct an organic silicon skeleton with a unique embeddable cavity structure by controlling the crosslinking degree and crosslinking size, which is used for the "embedded" anchor bolts of inorganic materials, thereby giving the material excellent thermal insulation, heat resistance and physical strength. At the same time, the molecular weight of the vinyl linear / branched phenyl silicone resin of the present invention is appropriate, which can effectively reduce the viscosity of the system and is suitable for injection molding process.
[0066] (2) The present invention utilizes silazane to modify fumed silica in situ, thereby reducing the silanol content on the surface of silica, reducing the molecular gap, reducing the oil absorption, and improving the tensile strength of the composite silicone resin; further utilizing the surface interface, quantum size and other nano-properties of fumed silica to coat inorganic flame retardant powders such as spherical alumina to form a particle-type core-shell structure, thereby improving the dispersibility of the inorganic powder in the silicone resin and improving the fluidity of the raw material, thereby making the raw material suitable for injection molding processing.
[0067] (3) The present invention utilizes temperature-responsive butyl succinic anhydride to control the concentration of 3,5-propyl-1-butyn-3-ol. When the temperature is higher than 50°C, butyl succinic anhydride changes from solid to liquid, thereby increasing the reaction rate with 3,5-propyl-1-butyn-3-ol and rapidly consuming 3,5-propyl-1-butyn-3-ol. The efficiency of the catalyst is released, and the organic acid generated by the reaction can further improve the efficiency of the catalyst, thereby achieving temperature-responsive triggered catalytic rapid curing.
[0068] (4) The present invention utilizes the excellent thermal insulation of hollow glass microspheres to reduce the heat conduction rate, prolong the high temperature contact time of the silicone material, reduce the carbonization rate of the silicone material, and improve the density of the ceramic layer. The ability of hollow glass microspheres to not "gasify" is utilized to increase the overall residual amount of the silicone material after high temperature burning, and to increase the residue coverage rate of the coated metal surface; the melting ability of hollow glass microspheres at high temperatures is utilized to improve the structural integrity of the ceramic layer. DETAILED DESCRIPTION
[0069] The present invention will be further described below in conjunction with the embodiments.
[0070] Overall embodiment
[0071] Vinyl linear phenyl silicone resin A:
[0072]
[0073] Among them, X=1-10, Y=3-10.
[0074] The preparation method is as follows: under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane and dimethyldiethoxysilane are uniformly mixed, and the mixture is dripped into an ice-salt bath pot, and the temperature is controlled at -15 to 0 DEG C. After the dripping is completed, the mixture is heated to room temperature to continue the reaction, and dimethylvinylchlorosilane is dripped to carry out a capping reaction, during which generated HCl is separated. After the dripping is completed, the inert gas protection is withdrawn, and the mixture is heated to 70-90 DEG C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation, and the mixture is heated to 140-160 DEG C to carry out structural reforming to obtain a vinyl straight-chain phenyl silicone resin A with a molecular weight of 600-3800.
[0075] Vinyl linear phenyl silicone resin B:
[0076]
[0077] Among them, x=1-10, y=3-6.
[0078] The preparation method is as follows: under the protection of an inert gas with a water content of 0.05-0.1wt%, dimethyldichlorosilane and diphenyldiethoxysilane are uniformly mixed, and the mixture is dripped into an ice-salt bath pot, and the temperature is controlled at -15 to 0 DEG C. After the dripping is completed, the mixture is heated to room temperature, and dimethylvinylchlorosilane is dripped to carry out a capping reaction, during which generated HCl is separated. After the dripping is completed, the inert gas protection is withdrawn, and the mixture is heated to 70-90 DEG C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation. The mixture is heated to 140-160 DEG C to carry out structural reforming, and a vinyl straight-chain phenyl silicone resin B with a molecular weight of 600-3800 is obtained.
[0079] Vinyl branched phenyl silicone resin C (alternating type):
[0080]
[0081] Among them, x=1-10, y=3-10, z=5-10, a=0-7, and a is more preferably 1-4.
[0082] The preparation method is as follows: under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane, vinylalkyldichlorosilane with a side alkyl carbon number of 1-8 and dimethyldiethoxysilane are uniformly mixed, and the mixture is dripped into an ice-salt bath pot, and the temperature is controlled at -15 to 0 DEG C. After the dripping is completed, the mixture is heated to room temperature to continue the reaction, and trimethylchlorosilane is dripped to carry out a capping reaction, during which generated HCl is separated. After the dripping is completed, the inert gas protection is withdrawn, and the mixture is heated to 70-90 DEG C to continue the reaction, and low-boiling substances are removed by reduced pressure distillation, and the mixture is heated to 140-160 DEG C to carry out structural reforming to obtain a vinyl branched phenyl silicone resin C with a molecular weight of 600-3800.
[0083] Vinyl branched phenyl silicone resin D (block type):
[0084]
[0085] Among them, X=1-10, Y=3-10, Z=5-10, a=0-7, and a is more preferably 1-4.
[0086] The preparation method is as follows: under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane and vinylalkyldichlorosilane with a carbon number of a side alkyl group of 1-8 are uniformly mixed, and the mixture is dripped into an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the dripping is completed, the mixture is heated to room temperature and then methylphenyldiethoxysilane is added, and the reaction is continued for a period of time, and trimethylchlorosilane is dripped for end-capping reaction, during which generated HCl is separated. After the dripping is completed, the inert gas protection is withdrawn, and then the mixture is heated to 70-90°C for further reaction, and low-boiling substances are removed by reduced pressure distillation, and the mixture is heated to 140-160°C for structural reforming to obtain a vinyl branched-chain phenyl silicone resin D with a molecular weight of 600-3800.
[0087] An injection moldable ceramic organic silicon fireproof material is obtained by mixing components including component A and component B uniformly and then heating and curing; the mass ratio of component A to component B is 0.5-1.5:1. Among them:
[0088] Component A includes the following raw materials in mass percentage: 15-30% of vinyl straight-chain phenyl silicone resin A and / or 15-30% of vinyl straight-chain phenyl silicone resin B, 0-2.5% of silicon micropowder, 0-2.5% of silazane-modified fumed silica, 0-5% of modified hydrogen-containing silicone oil 1, 0-5% of modified hydrogen-containing silicone oil 2, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of zinc borate, 5-15% of hollow glass microspheres, and 0-1% of a reaction rate regulator.
[0089] Component B includes the following raw materials in percentage by mass: 10-35% of vinyl branched phenyl silicone resin C and / or vinyl branched phenyl silicone resin D, 0-2.5% of silicon micropowder, 0-2.5% of silazane-modified fumed silica, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of hollow glass microspheres, 0-5% of adhesion promoter, and 0.1-0.3% of catalyst.
[0090] In component A:
[0091] The molecular structure formula of modified hydrogenated silicone oil is H1: Among them: M=1-5; N=2-10.
[0092] The molecular structure formula of modified hydrogenated silicone oil II is H2: Among them: m=1-5; n=2-10.
[0093] The reaction rate regulator is prepared by mixing butyl succinic anhydride and 3,5-propyl-1-butyn-3-ol in an excess amount of alcohol.
[0094] In component B: the adhesion promoter is obtained by uniformly mixing 0-30wt% of a titanate compound, 0-20wt% of KH151, 0-20wt% of KH560 and 20-50wt% of a vinyl linear phenyl silicone resin A and / or B, heating to 80-90°C, reacting for 3-4h, and then distilling off the low-boiling substances under reduced pressure. The catalyst is a platinum catalyst.
[0095] A method for preparing an injection moldable ceramic organic silicon fireproof material comprises the following steps:
[0096] S1: Vinyl straight-chain phenyl silicone resin A and / or B, silicon powder, silazane-modified fumed silica, modified hydrogenated silicone oil 1, modified hydrogenated silicone oil 2, spherical alumina with an average particle size of 80-120 μm, mica powder with an average particle size of 10-20 μm, zinc borate, hollow glass microspheres with an average particle size of 50-80 μm, and a reaction rate regulator are mixed and stirred at a temperature below 40°C and a vacuum degree of -0.01 to -0.07 MPa to obtain component A.
[0097] S2: Preparation of component B: Vinyl branched phenyl silicone resin C and / or D, silicon powder, silazane-modified fumed silica, spherical alumina with an average particle size of 80-120 μm, mica powder with an average particle size of 10-20 μm, hollow glass microspheres with an average particle size of 50-80 μm, adhesion promoter, and catalyst are mixed and stirred at a temperature below 40°C and a vacuum degree of -0.01 to -0.07 MPa to obtain component B.
[0098] S3: Mix component A and component B evenly, heat to ≥50°C for curing, and cure within 1 minute. Specific embodiments
[0100] Example 1: Preparation of resin Preparation of vinyl straight-chain phenyl silicone resin (A): Under nitrogen protection with a water content of 0.1wt%, methylphenyldichlorosilane (95.6g, 0.5mol) and dimethyldiethoxysilane (74.1g, 0.5mol) were mixed evenly and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. After 6h of addition, the temperature was raised to room temperature. After continuing the reaction for 12h, dimethylvinylchlorosilane (12.1g, 0.1mol) was slowly added dropwise for end-capping reaction, during which the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and the temperature was then raised to 80°C. After continuing the reaction for 12h, low-boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl straight-chain phenyl silicone resin A with a molecular weight of 600-3800.
[0101] Preparation of vinyl straight-chain phenyl silicone resin (B): Under nitrogen protection with a water content of 0.1wt%, dimethyldichlorosilane (95.6g, 0.5mol) and diphenyldiethoxysilane (136.2g, 0.5mol) were mixed evenly and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. After 6h of addition, the mixture was heated to room temperature and continued to react for 12h. Then, dimethylvinylchlorosilane (12.1g, 0.1mol) was slowly added dropwise for end-capping reaction. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and the mixture was heated to 80°C. After continuing to react for 12h, low-boiling substances were removed by reduced pressure distillation, and the mixture was heated to 150°C for structural reforming to obtain a vinyl straight-chain phenyl silicone resin B with a molecular weight of 600-3800.
[0102] Preparation of vinyl branched phenyl silicone resin (C-1) containing methyl side groups: Under nitrogen protection with a water content of 0.1wt%, methylphenyldichlorosilane (76.4g, 0.4mol), methylvinyldichlorosilane (14.1g, 0.1mol) and dimethyldiethoxysilane (74.1g, 0.5mol) were mixed evenly and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. After 6h of addition, the temperature was raised to room temperature. After continuing the reaction for 12h, trimethylchlorosilane (10.9g, 0.1mol) was slowly added dropwise for end-capping reaction. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and then the temperature was raised to 80°C. After continuing the reaction for 12h, the low-boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin C-1 containing methyl side groups with a molecular weight of 600-3800.
[0103] Preparation of vinyl branched phenyl silicone resin containing ethyl side groups (C-2): Under nitrogen protection with a water content of 0.1wt%, methylphenyldichlorosilane (76.4g, 0.4mol), ethylvinyldichlorosilane (15.4g, 0.1mol) and dimethyldiethoxysilane (74.1g, 0.5mol) were mixed evenly and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. After 6h of addition, the temperature was raised to room temperature. After continuing the reaction for 12h, trimethylchlorosilane (10.9g, 0.1mol) was slowly added dropwise for end-capping reaction. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and then the temperature was raised to 80°C. After continuing the reaction for 12h, the low-boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain vinyl branched phenyl silicone resin C-2 containing ethyl side groups with a molecular weight of 600-3800.
[0104] Preparation of vinyl branched phenyl silicone resin (C-3) containing octyl side groups: Under nitrogen protection with a water content of 0.1wt%, methylphenyldichlorosilane (76.4g, 0.4mol), octylvinyldichlorosilane (23.8g, 0.1mol) and dimethyldiethoxysilane (74.1g, 0.5mol) were mixed evenly and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. After 6h of addition, the temperature was raised to room temperature. After continuing the reaction for 12h, trimethylchlorosilane (10.9g, 0.1mol) was slowly added dropwise for end-capping reaction. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and then the temperature was raised to 80°C. After continuing the reaction for 12h, the low-boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain vinyl branched phenyl silicone resin C-3 containing octyl side groups with a molecular weight of 600-3800.
[0105] Preparation of vinyl branched phenyl silicone resin (D) containing methyl side groups: Under nitrogen protection with a water content of 0.1wt%, methylphenyldichlorosilane (76.4g, 0.4mol), methylvinyldichlorosilane (14.1g, 0.1mol) and mixed evenly were added dropwise to an ice-salt bath pot, the temperature was controlled at -5°C, and the addition was completed after 6h. After the temperature was raised to room temperature, methylphenyldiethoxysilane (105.17g, 0.5mol) was added. After continuing the reaction for 12h, trimethylchlorosilane (10.9g, 0.1mol) was added dropwise for end-capping reaction, during which the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, and then the temperature was raised to 80°C. After continuing the reaction for 12h, low boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin D containing methyl side groups with a molecular weight of 600-3800.
[0106] Preparation of vinyl branched phenyl silicone resin containing methyl side groups (D-1): The difference from the preparation method of vinyl branched phenyl silicone resin containing methyl side groups (D) is that nitrogen with a water content of 1wt% is used. As a result, due to the high water content, the reaction rate is too fast, gelation occurs, and the product cannot be obtained.
[0107] Example 2: Preparation of fireproof material The fireproof material is prepared by uniformly mixing component A and component B in a weight ratio of 1:1 and curing by heating.
[0108] Component A is specifically as follows: 15-30wt% of vinyl straight-chain phenyl silicone resin, 0-2.5wt% of silicon powder, 0-2.5wt% of silazane-modified fumed silica, 0-5wt% of modified hydrogenated silicone oil 1, 0-5wt% of modified hydrogenated silicone oil 2, 5-20wt% of spherical alumina, 10-25wt% of mica powder, 5-15wt% of zinc borate, 5-15wt% of hollow glass microspheres, and 0-1wt% of a reaction rate regulator.
[0109] Among them, modified hydrogen-containing silicone oil 1 (H1) and modified hydrogen-containing silicone oil 2 (H2) are provided by Zhejiang Hengyecheng Organic Silicone Co., Ltd., and their structural formulas are H1: and H2: Wherein: M = 1-5; N = 2-10; m = 1-5; n = 2-10. Silazane-modified fumed silica was purchased from Wacker Chemie, and the reaction rate regulator was prepared by mixing butyl succinic anhydride and 3,5-propyl-1-butyn-3-ol with an excess of alcohol (molar ratio 1:1.1).
[0110] Preparation of component A (A1): 30 parts of vinyl straight-chain phenyl silicone resin (A), 2.5 parts of silicon powder, 2.5 parts of silazane-modified fumed silica, 4 parts of modified hydrogenated silicone oil 1 (H1), 5 parts of modified hydrogenated silicone oil 2 (H2), 10 parts of spherical alumina (average particle size 100 microns), 25 parts of mica powder (average particle size 15 microns), 5 parts of zinc borate, 15 parts of hollow glass microspheres (average particle size 65 microns), and 1 part of reaction rate regulator are added to a high-speed dispersing planetary mixer, the temperature is controlled below 40°C, mixed and stirred for 2 hours, the vacuum degree is -0.07 MPa, and the material is discharged after stirring evenly to obtain component A1.
[0111] Preparation of component A (A2): 30 parts of vinyl straight-chain phenyl silicone resin (B), 2.5 parts of silicon powder, 2.5 parts of silazane-modified fumed silica, 4 parts of modified hydrogenated silicone oil 1 (H1), 5 parts of modified hydrogenated silicone oil 2 (H2), 20 parts of spherical alumina (average particle size 100 microns), 15 parts of mica powder (average particle size 15 microns), 5 parts of zinc borate, 15 parts of hollow glass microspheres (average particle size 65 microns), and 1 part of reaction rate regulator are added to a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07 MPa, and the material is discharged after stirring evenly to obtain component A2.
[0112] Preparation of component A (A3): 30 parts of vinyl straight-chain phenyl silicone resin (B), 2.5 parts of silicon powder, 2.5 parts of silazane-modified fumed silica, 4 parts of modified hydrogenated silicone oil 1 (H1), 5 parts of modified hydrogenated silicone oil 2 (H2), 20 parts of spherical alumina (average particle size 100 microns), 10 parts of mica powder (average particle size 15 microns), 5 parts of zinc borate, 20 parts of hollow glass microspheres (average particle size 65 microns), and 1 part of reaction rate regulator are added to a high-speed dispersing planetary mixer, the temperature is controlled below 40°C, mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component A3.
[0113] Component B is specifically as follows: 10-35wt% of vinyl branched phenyl silicone resin, 0-2.5wt% of silicon powder, 0-2.5wt% of silazane-modified fumed silica, 5-20wt% of spherical alumina, 10-25% of mica powder, 5-15wt% of hollow glass microspheres, 0-5wt% of adhesion promoter, and 0.1-0.3wt% of platinum catalyst.
[0114] The adhesion promoter is prepared by mixing titanate compound (20%), KH151 (15%), KH560 (15%) and vinyl straight-chain phenyl silicone resin A (50%), heating to 85°C, reacting for 4 hours, and then distilling off low-boiling substances under reduced pressure to obtain the adhesion promoter. The platinum catalyst is KARSTEDT. Spherical alumina, mica powder and hollow glass microspheres are consistent with the corresponding raw materials used in component A.
[0115] Preparation of component B (B1): 35 parts of vinyl branched phenyl silicone resin containing methyl side groups (C-1), 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 20 parts of spherical alumina, 20 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst are added into a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component B1.
[0116] Preparation of component B (B2): 35 parts of vinyl branched phenyl silicone resin (D), 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 20 parts of spherical alumina, 20 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst are added into a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component B2.
[0117] Preparation of component B (B3): 35 parts of vinyl branched phenyl silicone resin (D), 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 15 parts of spherical alumina, 25 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst are added into a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component B3.
[0118] Preparation of component B (B4): 35 parts of vinyl branched phenyl silicone resin containing ethyl side groups (C-2), 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 20 parts of spherical alumina, 20 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst are added into a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component B4.
[0119] Preparation of component B (B5): 35 parts of vinyl branched phenyl silicone resin (C-3) containing octyl side groups, 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 20 parts of spherical alumina, 20 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst are added into a high-speed dispersing planetary mixer, the temperature is controlled below 40°C and mixed and stirred for 2 hours, the vacuum degree is -0.07Mpa, and the material is discharged after stirring evenly to obtain component B5.
[0120] After the components A and B are mixed evenly at a ratio of 1:1, the viscosity of the material changes little below 40°C, and the material is cured within 1 minute after heating to 60°C. The present invention uses butyl succinic anhydride to achieve a temperature-responsive triggering catalytic method, which has unique advantages and is particularly suitable for injection molding.
[0121] Curing example:
[0122] Curing example 1: A1+B1;
[0123] Curing example 2: A2+B2;
[0124] Curing example 3: A3+B3;
[0125] Curing example 4: A1+B4;
[0126] Curing Example 5: A1+B5.
[0127] Comparative Example
[0128] Comparative Example 1: Compared with Curing Example 1, the difference is that Component A does not contain vinyl linear phenyl silicone resin (A), and is replaced by an equal mass of vinyl branched phenyl silicone resin (C-1) (i.e., both Components A and B are branched phenyl silicone resins).
[0129] The formula of component A (Component A4) is: 30 parts of vinyl branched phenyl silicone resin (C-1), 2.5 parts of silicon powder, 2.5 parts of silazane-modified fumed silica, 4 parts of modified hydrogenated silicone oil 1 (H1), 5 parts of modified hydrogenated silicone oil 2 (H2), 10 parts of spherical alumina (particle size 100 microns), 25 parts of mica powder (particle size 15 microns), 5 parts of zinc borate, 15 parts of hollow glass microspheres (65 microns), and 1 part of reaction rate regulator.
[0130] Comparative Example 2: Compared with Curing Example 1, the difference is that Component B does not contain vinyl branched phenyl silicone resin (C-1), and is replaced by an equal mass of vinyl straight-chain phenyl silicone resin (A) (i.e., Components A and B are both straight-chain phenyl silicone resins).
[0131] The formula of component B (B6) is: 35 parts of vinyl linear phenyl silicone resin (A), 2.5 parts of silicon micropowder, 2.5 parts of silazane-modified fumed silica, 20 parts of spherical alumina, 20 parts of mica powder, 15 parts of hollow glass microspheres, 4.8 parts of adhesion promoter, and 0.2 parts of KARSTEDT catalyst.
[0132] Comparative Example 3: Compared with Curing Example 1, the difference is that the vinyl linear phenyl silicone resin in component A (A5) and the vinyl branched phenyl silicone resin in component B (B7) are both high molecular weight. The molecular weight of the vinyl linear phenyl silicone resin is 5000-20000, and the molecular weight of the vinyl branched phenyl silicone resin is 5000-20000.
[0133] Comparative Example 4: Compared with Curing Example 1, the difference is that the reaction rate regulator of component A (component A6) does not contain butyl succinic anhydride.
[0134] Performance Testing
[0135] The performance of the organic silicon fireproof material obtained by mixing and curing different components A and B was tested, and the data are shown in the following table:
[0136]
[0137] * 1 The method for measuring the temperature of the back side of the coating is to measure the temperature of the back side after the front side of the 0.3 mm coating has been continuously sprayed with the above-mentioned high-temperature flame for 30 minutes.
[0138] * 2 The commercially available product (Comparative Example 5) is an organic silicon thermal insulation coating prepared by molding technology (provided by Ningbo Juli Company).
[0139] By comparing the data in the above table, we can see that:
[0140] Curing Examples 1-5: Curing Examples 1-5 have excellent performance in terms of viscosity before curing, curing time, and tensile strength, fireproof temperature, back temperature of coating, and flame retardant grade of cured materials, which are significantly better than the commercially available product of Comparative Example 5. They are not only suitable for injection molding processes, but also have greatly shortened curing time, and can be cured within 1 minute. Among them, the difference between Curing Examples 1, Curing Examples 4, and Curing Examples 5 is that vinyl branched phenyl silicone resins with different lengths of alkyl side groups are used in component A (Curing Example 1 is a methyl side group, Curing Example 4 is an ethyl side group, and Curing Example 5 is an octyl side group). The ethyl side group of Curing Example 4 and the octyl side group of Curing Example 5 can be better entangled with the side groups on other molecular chains during the curing reaction compared to the methyl side group of Curing Example 1, so that a material with higher tensile strength can be obtained. However, since the length of the octyl side group of Curing Example 5 is longer than that of the methyl and ethyl groups, the viscosity of the system will be increased to a certain extent.
[0141] Comparative Examples 1-4: Compared with Curing Example 1, Comparative Example 1 differs in that both components A and B are vinyl branched phenyl silicone resins and do not contain vinyl straight-chain phenyl silicone resins. The disadvantage is that the system viscosity of pure vinyl branched phenyl silicone resins will increase, resulting in insufficient cross-linking reaction during the curing stage, which ultimately leads to a decrease in the various properties of the material. Compared with Curing Example 1, Comparative Example 2 differs in that both components A and B are vinyl straight-chain phenyl silicone resins. Although the system viscosity will be lower, the compounding of branched vinyl and straight-chain vinyl can produce a higher degree of cross-linking after curing than pure straight-chain vinyl, so it is more conducive to improving the various properties of the material (especially tensile strength). Compared with Curing Example 1, Comparative Example 3 differs in that components A and B use higher molecular weight vinyl phenyl silicone resins, which leads to a sharp increase in the system viscosity, and can only be barely injected. The performance of the obtained material after curing is also poor. The difference between Comparative Example 4 and Curing Example 1 is that the reaction rate regulator of Component A does not contain butyl succinic anhydride, which greatly slows down the reaction of 3,5-propyl-1-butyn-3-ol during the curing stage, resulting in a significant increase in the curing time and a significant decrease in the performance of the resulting material.
[0142] Comparative Example 5: Comparative Example 5 is a similar molded product available on the market. It can be seen that the injection molding process used in the present invention is superior to the compression molding process, has a shorter curing time, and has better performance in all aspects.
[0143] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0144] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a vinyl straight-chain phenyl silicone resin, characterized in that include: Under the protection of an inert gas with a water content of 0.05-0.1wt%, methylphenyldichlorosilane and dimethyldiethoxysilane are uniformly mixed and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature, and dimethylvinylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by vacuum distillation. The temperature is raised to 140-160°C for structural reforming to obtain a vinyl straight-chain phenyl silicone resin with the following structural formula: Among them, X=1-10, Y=3-10.
2. A method for preparing a vinyl straight-chain phenyl silicone resin, characterized in that include: Under the protection of an inert gas with a water content of 0.05-0.1wt%, dimethyldichlorosilane and diphenyldiethoxysilane are uniformly mixed and added dropwise to an ice-salt bath pot, and the temperature is controlled at -15 to 0°C. After the addition is completed, the temperature is raised to room temperature, and dimethylvinylchlorosilane is added dropwise for end-capping reaction, during which the generated HCl is separated. After the addition is completed, the inert gas protection is withdrawn, and then the temperature is raised to 70-90°C to continue the reaction, and low-boiling substances are removed by vacuum distillation. The temperature is raised to 140-160°C for structural reforming to obtain a vinyl straight-chain phenyl silicone resin with the following structural formula: Among them, x=1-10, y=3-6.
3. A method for preparing a vinyl branched phenyl silicone resin with an alternating structure, characterized in that include: Under nitrogen protection with a water content of 0.1wt%, 0.4mol of methylphenyldichlorosilane, 0.1mol of methylvinyldichlorosilane and 0.5mol of dimethyldiethoxysilane were mixed and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. The addition was completed after 6h, and the temperature was raised to room temperature. The reaction was continued for 12h. 0.1mol of trimethylchlorosilane was added dropwise for end-capping. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, the temperature was raised to 80°C, and the reaction was continued for 12h. Low boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin with an alternating structure and a molecular weight of 600-3800.
4. A method for preparing a vinyl branched phenyl silicone resin with an alternating structure, characterized in that include: Under nitrogen protection with a water content of 0.1wt%, 0.4mol of methylphenyldichlorosilane, 0.1mol of ethylvinyldichlorosilane and 0.5mol of dimethyldiethoxysilane were mixed and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. The addition was completed after 6 hours, and the temperature was raised to room temperature. The reaction was continued for 12 hours. 0.1mol of trimethylchlorosilane was added dropwise for end-capping. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, the temperature was raised to 80°C, and the reaction was continued for 12 hours. Low boiling materials were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin with an alternating structure and a molecular weight of 600-3800.
5. A method for preparing a vinyl branched phenyl silicone resin with an alternating structure, characterized in that include: Under nitrogen protection with a water content of 0.1wt%, 0.4mol of methylphenyldichlorosilane, 0.1mol of octylvinyldichlorosilane and 0.5mol of dimethyldiethoxysilane were mixed and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. The addition was completed after 6 hours, and the temperature was raised to room temperature. The reaction was continued for 12 hours. 0.1mol of trimethylchlorosilane was added dropwise for end-capping. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, the temperature was raised to 80°C, the reaction was continued for 12 hours, low-boiling substances were removed by reduced pressure distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin with an alternating structure and a molecular weight of 600-3800.
6. A method for preparing a vinyl branched phenyl silicone resin with a block structure, characterized in that include: Under nitrogen protection with a water content of 0.1wt%, 0.4mol of methylphenyldichlorosilane and 0.1mol of methylvinyldichlorosilane were mixed and added dropwise to an ice-salt bath pot. The temperature was controlled at -5°C. The addition was completed after 6 hours. After warming to room temperature, 0.5mol of methylphenyldiethoxysilane was added and the reaction was continued for 12 hours. 0.1mol of trimethylchlorosilane was added dropwise for end-capping. During this period, the generated HCl was separated. After the addition was completed, the nitrogen protection was removed, the temperature was raised to 80°C, the reaction was continued for 12 hours, low-boiling substances were removed by vacuum distillation, and the temperature was raised to 150°C for structural reforming to obtain a vinyl branched phenyl silicone resin with a molecular weight of 600-3800 and a block structure.
7. An injection moldable ceramic organic silicon fireproof material, characterized in that: The components including component A and component B are mixed evenly and then heated and cured; wherein: Component A comprises the following raw materials in mass percentage: 15-30% of the vinyl straight-chain phenyl silicone resin obtained by the preparation method according to claim 1 and / or the vinyl straight-chain phenyl silicone resin obtained by the preparation method according to claim 2, 0-2.5% of silicon powder, 0-2.5% of silazane-modified fumed silica, 0-5% of modified hydrogenated silicone oil 1, 0-5% of modified hydrogenated silicone oil 2, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of zinc borate, 5-15% of hollow glass microspheres, and 0-1% of a reaction rate regulator; Component B comprises the following raw materials in percentage by mass: 10-35% of a vinyl branched phenyl silicone resin with an alternating structure obtained by the preparation method according to any one of claims 3 to 5 and / or a vinyl branched phenyl silicone resin with a block structure obtained by the preparation method according to claim 6, 0-2.5% of silicon micropowder, 0-2.5% of silazane-modified fumed silica, 5-20% of spherical alumina, 10-25% of mica powder, 5-15% of hollow glass microspheres, 0-5% of an adhesion promoter, and 0.1-0.3% of a catalyst; The contents of the above raw materials are all > 0; The structural formula of modified hydrogenated silicone oil is M = 1-5; N = 2-10; The structural formula of modified hydrogenated silicone oil II is m=1-5; n=2-10.
8. The injection moldable ceramic organic silicon fireproof material according to claim 7, characterized in that: In the component A, the reaction rate regulator is prepared by mixing butyl succinic anhydride and 3,5-propyl-1-butyn-3-ol in an excess amount of alcohol.
9. The injection moldable ceramic organic silicon fireproof material according to claim 7 or 8, characterized in that: The viscosity of the injection moldable ceramic organic silicon material before curing is ≤25 Pa·S, the curing time is ≤1 min, and the tensile strength after curing is ≥2.3 MPa.
10. A method for preparing an injection moldable ceramic organic silicon fireproof material as claimed in claim 7 or 8, characterized in that The steps include: S1: Mix and stir the vinyl straight-chain phenyl silicone resin obtained by the preparation method of claim 1 and / or the vinyl straight-chain phenyl silicone resin obtained by the preparation method of claim 2, silicon powder, silazane-modified fumed silica, modified hydrogen-containing silicone oil 1, modified hydrogen-containing silicone oil 2, spherical alumina, mica powder, zinc borate, hollow glass microspheres, and a reaction rate regulator at a temperature below 40° C. and a vacuum degree of -0.01 to -0.07 MPa to obtain component A; S2: Preparation of component B: Mix and stir the vinyl branched phenyl silicone resin with an alternating structure obtained by the preparation method according to any one of claims 3 to 5 and / or the vinyl branched phenyl silicone resin with a block structure obtained by the preparation method according to claim 6, silicon powder, silazane-modified fumed silica, spherical alumina, mica powder, hollow glass microspheres, adhesion promoter, and catalyst at a temperature below 40° C. and a vacuum degree of -0.01 to -0.07 MPa to obtain component B; S3: Mix component A and component B evenly, and heat to ≥50°C for curing.
11. The preparation method according to claim 10, characterized in that: The viscosity of the injection moldable ceramic organic silicon material before curing is ≤25 Pa·S, the curing time is ≤1 min, and the tensile strength after curing is ≥2.3 MPa.
Citation Information
Patent Citations
Preparation method of methyl phenyl vinyl silicon resin for packaging light-emitting diode (LED)
CN101979427A
Synthesis method for phenyl organosilicon copolymer with uniformly distributed phenyl units
CN102604101A